Development of socio-technical approach for landslide mitigation and risk reduction progra in Indonesia. - Karnawati, Dwikorita (Asean Engineering Journal)
Intensive efforts for mitigating and reducing the risk of landslides in Indonesia have been conducted since more than 30 years ago. But still, substantial socio-economical losses continuously occur as the results of landslide disasters. Admittedly, the natural conditions plays important role in controlling the susceptibility and triggering the occurence of landslides. Yet, the human interfere and landuse changing crucially contribute in the triggering process of landslides. Indeed, the increase in societal impacts due to the landslide disasters also strongly related to the landuse changing, driven by the social constrains. Unfortunately, the technical solution for landslide mitigation and risk reduction does not always appropriately address the socio cultural and socio economical aspects of the disaster prone area. That is why, the hybrid socio-technical system is promoted in this study, in which not only the engineering but also social system has to be system was mainly supported by the participatory landslide hazard and risk map as well as the community based landslide early warning system. Such system was developed by enhancing the local knowledge, through the local participation and utilizing the local materials. Meanwhile, the social system was established through a series of community empowerment programs and supported by the establishment of local task force for disaster risk reduction at the village. Accordingly, the developed system can be effectively operated, maintained and sustained by the local community. Indeed, the roles of the local task force and the local university are very important to drive and ensure the effectiveness of the landslide mitigation and disaster risk reduction